In vitro antibacterial activity of medicinal plants against biofilm-forming methicillin-resistant Staphylococcus aureus: efficacy of Moringa stenopetala and Rosmarinus officinalis extracts. Issue 1 (January 2020) - Manilal, Aseer; Sabu, Kuzhunellil Raghavanpillai; Shewangizaw, Misgun; Aklilu, Addis; Seid, Mohammed; Merdekios, Behailu; Tsegaye, Behailu
Abstract: The prevalence of methicillin-resistant Staphylococcus aureus (MRSA) is slowly rising in Ethiopia for the past few decades. Therefore, novel classes of antibiotics are indispensable to combat the increased incidence of newly emerging multidrug-resistant bacteria like MRSA. Terrestrial flora is considered as a reservoir of novel bioactive secondary metabolites as they have provided us with the largest array of natural products. In this background, the present study is intended to evaluate the in-vitro antibacterial efficacy of five medicinal plants ( Ocimum lamiifolium Hochst. ex Benth., Rosmarinus officinalis L, Catharanthus roseus Linn., Azadirachta indica A. Juss and Moringa stenopetala Bac) against a panel of seven biofilm-forming MRSA. The leaves of the plants were extracted in organic solvents of varying polarity and the resultant crude extracts of respective medicinal plants were inspected for their antimicrobial activity by well diffusion technique. Minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) of the plant extracts against MRSA were determined by the broth dilution method. Besides, an anti-biofilm assay of the most potent plant extract was also performed, after which its chemical constituents were delineated by combined Gas Chromatographic and Mass Spectroscopic profiling (GC-MS). The results revealed that, of the five plants, three species including M. stenopetala, R. officinalis, and O. lamifolium exhibited significant antibacterial activity. Organic solvents with high and medium polarity were excellent in extracting antimicrobials compared to nonpolar solvents. The broadest and highest rank of activity was observed in the crude ethanolic extract of M. stenopetala. Based on the MIC/MBC ratio, the crude ethanolic extract of M. stenopetala was determined to be bacteriostatic. Anti-biofilm assay showed that the extract of M. stenopetala fairly inhibited the growth of MRSA in the preformed biofilm matrix. The GC-MS analysis of M. stenopetala revealed the presence of twelve compounds with antimicrobial activity. The present study provides new insight into the development of novel drug leads to the management of MRSA. Abstract : Microbiology; Biotechnology; Metabolite; Medical Microbiology; Antimicrobial; MRSA; Antibacterial activity; anti-biofilm activity; Moringa stenopetala ; Plant extract